ORGANIZATIONAL CREATIVITY IN INNOVATION – A MULTICRITERIA DECISION ANALYSIS - Fellipe Silva Martins (Independent Journal of Management & Production, 2017)
Creativity is essential for the emergence of innovation within organizations, both neces sary for organizational survival. Several models have been proposed for organizational creativity, each containing different constructs. This research aims to verify the standardization of constructs in the literature and to verify the possible existence o f two dimensions not previously explored: hierarchy between constructs (global importance) and weight of constructs (relative importance) of organizational creativity that lead to innovation. We employed Multicriteria Decision Analysis with the PAPRIKA met hod, which combines the advantages of numerical and verbal decision making. The creativity constructs were elicited from a detailed review of the literature from Scopus and Web of Science databases. The results contribute to the expansion of the current th eory of creativity, with the application of a new method to the object and management practices.